Velocity and stride parameters in the 400 Metres - Gajer, B.; Hanon, C.; Thepaut-Mathieu, C. (New Studies in Athletics, 2007)
Success in the 400m requires the athlete to preserve the optimal technical characteristics of his/her stride despite intense fatigue. Using 50m intervals, the time courses of velocity and stride parameters (length and frequency) were evaluated for races of three groups of athletes: world-class, national level and regional level. The better athletes were able to achieve higher absolute and relative velocities (% of their best performance over 200m). These were reached by way of both significantly greater stride length and stride frequency. It is notable that peak values for the two parameters were observed in different parts of the race: between 50 and 100m for stride frequency and between 100 and 150m for stride length. In general, length rather than frequency is the stride parameter distinguishing the groups from each other. As the morphological characteristics of the subjects were similar, this could indicate greater maximal strength levels for the better athletes.